2015
DOI: 10.5152/balkanmedj.2015.15663
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Weighted Magnetic Resonance Imaging for the Characterization of Solitary Pulmonary Lesions

Abstract: Background:We evaluated the differential diagnosis of solitary pulmonary lesions on magnetic resonance imaging. Aims: To investigate the value of diffusion weighted imaging on the differential diagnosis of solitary pulmonary lesions. Study Design: Randomized prospective study. Methods: This prospective study included 48 solitary pulmonary nodules and masses (18 benign, 30 malignant). Single shot echo planar spin echo diffusion weighted imaging (DWI) was performed with two b factors (0 and 1000 s/mm 2 ). Appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 18 publications
0
20
1
Order By: Relevance
“…Lung lesions can be characterized on DWI by qualitative (visual assessment of the lesion), semiquantitative (ratio of the lesion to spinal cord signal intensities), and quantitative (ADC measurement) evaluation. Although the qualitative evaluation of the lung lesions has been showed to be successful, the subjectivity of this method may result in variations. The calculated ratio of signal intensity of the lesion to spinal cord (LSR) has been successfully used for differentiation of benign and malignant tumors .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Lung lesions can be characterized on DWI by qualitative (visual assessment of the lesion), semiquantitative (ratio of the lesion to spinal cord signal intensities), and quantitative (ADC measurement) evaluation. Although the qualitative evaluation of the lung lesions has been showed to be successful, the subjectivity of this method may result in variations. The calculated ratio of signal intensity of the lesion to spinal cord (LSR) has been successfully used for differentiation of benign and malignant tumors .…”
Section: Discussionmentioning
confidence: 99%
“…Satoh et al and Çakir et al qualitatively compared the signal intensity of the nodules with that of spinal cord on DWI, and found that malignant nodules were significantly more hyperintense than benign nodules. Satoh et al evaluated 54 pulmonary nodules and they obtained DWI using the free‐breathing technique and b value of 1000 s/mm 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations